2011
DOI: 10.1126/scisignal.2001227
|View full text |Cite
|
Sign up to set email alerts
|

Rho and Rho-Kinase Activity in Adipocytes Contributes to a Vicious Cycle in Obesity That May Involve Mechanical Stretch

Abstract: The development of obesity involves multiple mechanisms. Here, we identify adipocyte signaling through the guanosine triphosphatase Rho and its effector Rho-kinase as one such mechanism. Mice fed a high-fat diet (HFD) showed increased Rho-kinase activity in adipose tissue compared to mice fed a low-fat diet. Treatment with the Rho-kinase inhibitor fasudil attenuated weight gain and insulin resistance in mice on a HFD. Transgenic mice overexpressing an adipocyte-specific, dominant-negative form of RhoA (DN-RhoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 50 publications
6
100
0
Order By: Relevance
“…Low extracellular matrix stiffness and stretching (ie, decreased intracellular tension) promote adipogenesis, but compression impedes it. [60][61][62][63][64][65] In our study, less collagen deposition and capsule formation were found in the PCL group at the early and middle stages compared with the control group, which indicated lower extracellular matrix stiffness and intracellular tension in the tissue of the PCL group in this period. This collective finding explains why there were more adipogenic gene (PPARγ) expression at week 4 and larger volume of adipose tissue in the following weeks in the PCL group.…”
mentioning
confidence: 76%
“…Low extracellular matrix stiffness and stretching (ie, decreased intracellular tension) promote adipogenesis, but compression impedes it. [60][61][62][63][64][65] In our study, less collagen deposition and capsule formation were found in the PCL group at the early and middle stages compared with the control group, which indicated lower extracellular matrix stiffness and intracellular tension in the tissue of the PCL group in this period. This collective finding explains why there were more adipogenic gene (PPARγ) expression at week 4 and larger volume of adipose tissue in the following weeks in the PCL group.…”
mentioning
confidence: 76%
“…MLC 20 and myosin phosphatase target subunit 1 (MYPT-1) are ROCK-specific substrates (42)(43)(44). Previously, we reported that phosphorylation of MLC 20 at serine 19 residue is increased in the fibroblastic foci in human IPF (45).…”
Section: Figurementioning
confidence: 99%
“…(Myo)fibroblasts isolated from IPF lungs and lungs of mice after bleomycin injury demonstrated high constitutive ROCK activity, as indicated by ELISA-based ROCK activity assay, in comparison to their respective controls ( Figure 5B). Immunoblot analysis for phosphorylation of ezrin Thr567 /radixin Thr564 /moesin Thr558 (ERM), a group of ROCK-specific substrates that function as linkers between plasma membrane and actin cytoskeleton (42,46), demonstrated high baseline levels of phosphorylated ERM in fibrotic lung fibroblasts from mice and humans ( Figure 5C). Rhotekin pulldown assays, based on affinity precipitation of GTP-bound (i.e., active) RhoA using glutathione S-transferase-rhotekin (GST-RBD) fusion proteins and immunoblot analysis, demonstrated that (myo)fibroblasts isolated from fibrotic lungs expressed higher levels of active RhoA than cells isolated from control uninjured lungs ( Figure 5D).…”
Section: Figurementioning
confidence: 99%
“…Although there are very limited experimental findings concerning relaxing mechanical stress, inhibition of myosin II 21) 22) or Rho kinase 23) , both of which decrease actomyosin contractility, reportedly has antiinflammatory effects. Furthermore, adhesion to softer substrates has been reported to downregulate the NF-κB activity as well as the expression of pro-inflammatory cytokines 24) .…”
Section: Anti-inflammatory Effects Of Relaxing Mechanical Stressmentioning
confidence: 99%